PENGEMBANGAN MATERI AJAR EKOSISTEM UNTUK SMP MENGGUNAKAN PENDEKATAN SAINS TEKNOLOGI MASYARAKAT DAN TIM HIJAU SEKOLAH - Sukarsih Sukarsih (Center of Language and Cultural Studies, 2016)
This research was development of learning equipment research that have oriented at Kemp. It was implemented through Science Techonoloy Society Approach and School Green Team. The subject of this research were 39 students of SMP Negeri 3 Bontang assigned as One Group Pretest and Posttest Design. The research discovered the following findings: activity of Teacher’s School Green Team to guide student’s activity (25,31%), motivation (24,75%) and student activity observing (23,75%) with the degree of instrument reliability 87.70%. The rising of student’s activity indicated: observing (27,00%), sharing and discusion (25,23%) with the degree of instrument’s reliability average 98,47%. The completeness of student learning individually and classically were reached feasibility and the learning plan was in good category. Generally this research showed that learning by Science Technology Society Approach through School Green Team increased learning achievement.